FEBRILE SIEZURES : Risk Factors in ages 6 months to 5 Years in Tishreen university hospital from 2015to 2016 (Latakia University Journal -Medical Sciences Series, 2018)
Introduction : febrile seizures is the most common seizures in childhood , although it is benign , and self-limited, but it is a terrifying experience to the parents . Objective :study the relationship between febrile seizures and the studied risk factors( family history ,Iron deficiency anemia ,duration of Breast feeding ),and determine the most common infections accompanying febrile seizures. Methods: the study included 60 child (30 case ,30 control ) in same age and gender , which admitted to Tishreen university hospital , in the time of the study July 2015 to July 2016 ,case definition :child age 6 month to 5 years, has a fever and seizure ,control definition : child with fever ,without seizure in same age and gender . Results : result of the study of the relationship between febrile seizures and family history , we found (OR= 3.4), that means ,the risk to have febrile seizures is 3 times in children who have positive family history (febrile and Afebrile ),also we found that the risk is 2 times more in children who have Iron deficiency anemia (OR=2.4),results found that the risk to febrile seizures is 2 times more in children whose Breast feeding duration is short (OR=2.2). our study :Respiratory infections are most accompanying with febrile seizures (90%), Tonsillitis is the most respiratory infection (55.5%). الاختلاج الحروري : عوامل الخطورة للحدوث بين عمر 6 أشهر و5 سنوات, في مشفى تشرين الجامعي بين عامي 2015-2016 مقدمة: تعد الاختلاجات الحرورية أشيع اختلاجات الطفولة , ورغم أنها حميدة ومحددة لذاتها , إلا أنها تعد تجربة مرعبة للأهل . الهدف :دراسة العلاقة بين الاختلاج الحروري , وعوامل الخطورة المدروسة (القصة العائلية , فقر الدم بعوز الحديد , مدة الارضاع الوالدي ) ,و تحديد أشيع الانتانات المرافقة للاختلاج الحروري . الطرق : شملت الدراسة 60 طفلاً( 30 حالة مقابل 30 شاهد ), من نفس الجنس والفئة العمرية , المقبولين في مشفى تشرين الجامعي خلال مدة الدراسة من تموز 2015 ولغاية تموز 2016, الحالة : هي كل طفل بعمر بين 6أشهر وخمس سنوات , ولديه ترفع حروري مع اختلاج , الشاهد :طفل لديه ترفع حروري دون اختلاج حروري من نفس العمر والجنس . النتائج :نتيجة لدراسة العلاقة بين الاختلاج الحروري والقصة العائلية ,وجدنا بأن (OR = 3.4) هذا يعني أن الخطر أكثر ب3 مرة عند الأطفال ممن لديهم قصة عائلية إيجابية للاختلاجات (حرورية ولا حرورية ),كما وجدنا أن الخطر أكثر ب2 مرة عند الأطفال ممن لديهم فقر دم بعوز الحديد (OR = 2.4), بالدراسة وجدنا أن خطر حدوث الاختلاج الحروري أكثر ب 2 مرة عند الأطفال ممن كانت لديهم فترة الارضاع الوالدي قصيرة (OR=2.2 ) , بحسب دراستنا إن أشيع الانتانات المرافقة للاختلاج الحروري هي الانتانات التنفسية بنسبة 90%, والتهاب اللوز القيحي شكل النسبة الأعلى من الانتانات التنفسية 55.5% .